Evaluación de dos métodos para medir la sensibilidad de inhibición de crecimiento de la cepa certificada de Staphylococcus aureus subsp. aureus - Montero-Recalde, Mayra (2018)
The aim of this research was to evaluate two methods of sensitivity for the inhibition of the growth of Staphylococcus aureus subsp. aureus (ATCC® 11632), the Kirby-Bauer method and the modified agar wells, using honey 100% from Apis mellifera. The modified method in agar wells formed inhibition halos of 25.04 mm and that of Kirby-Bauer of 21.15 mm, indicating that the modified method in agar wells is more sensitive than the Kirby-Bauer method.The aim of this research was to evaluate two methods of sensitivity for the inhibition of the growth of Staphylococcus aureus subsp. aureus (ATCC® 11632), the Kirby-Bauer method and the modified agar wells, using honey 100% from Apis mellifera. The modified method in agar wells formed inhibition halos of 25.04 mm and that of Kirby-Bauer of 21.15 mm, indicating that the modified method in agar wells is more sensitive than the Kirby-Bauer method.